2015
DOI: 10.1016/j.apor.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

URANS studies of hydrodynamic performance and slamming loads on high-speed planing hulls in calm water and waves for deep and shallow conditions

Abstract: a b s t r a c t URANS capability for hydrodynamic performance and slamming of high speed planing crafts are assessed, using metrics specified for naval applications. Wedge drop validation studies using two different solvers, one single-phase and the other two-phase, shows good agreement with experimental data for time history of pressure gauges. Planing hull validation studies are carried out using the historical benchmark experiments of Fridsma. Simulation conditions include calm water in deep and shallow con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 12 publications
2
28
0
1
Order By: Relevance
“…VOF, mesh density, k-ε (Mousaviraad, Wang, & Stern, 2015) CFD ship-Iowa: unsteady RANS, single-phase, twophase…”
Section: Metode Analisismentioning
confidence: 99%
“…VOF, mesh density, k-ε (Mousaviraad, Wang, & Stern, 2015) CFD ship-Iowa: unsteady RANS, single-phase, twophase…”
Section: Metode Analisismentioning
confidence: 99%
“…Considering experimental data as the basis (Sukas et al 2017) achieved less error for simulations performed on the Fridsma hull form using overset grids (also known as chimera or overlapping grids) compared with single grid for high Froude numbers. Mousaviraad et al (2015) assessed the capability of unsteady Reynolds-averaged Navier-Stokesbased CFD Ship-Iowa solvers for hydrodynamic performance and slamming for high-speed planing vessels with validation and verification (V&V) studies performed using benchmark data of Fridsma. De Marco et al (2017) performed experimental and numerical investigations of flow for stepped planing hull using Reynolds-averaged Navier-Stokes (RANS) and large eddy simulations (LES), with different moving mesh techniques such as overset/chimera and morphing mesh; it is concluded that the overset grid gave better results among the methods.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Menurut beberapa literatur yang dilakukan oleh Yousefi pada tahun 2013, simulasi numerik dapat dilakukan untuk memprediksi fenomena aliran disekitar lambung kapal planing hull [4]. Beberapa penelitian menggunakan software Ansys-FLUENT [5], [6], Ansys-CFX [7], CFDship-Iowa [8], COMET [9], [10], ALE-VMS [11] dan Star-CCM+ [12]- [14].…”
Section: Pendahulanunclassified